Fish Protein Hydrolyzate From Grouper Epinephelus Offal Using Bromelain Enzyme Pineapple Crude Extract - Andi Nur Faiziah Palla; Metusalach; Nursinah Amir (Hasanuddin University, 2022)
Grouper is one of the demersal fish groups that are abundant in Indonesian marine waters. In addition, the high market demand for this fish has also increased its main production technique as an export product. One example of a product from this fish is fish fillet which still leaves waste. Offal is an example of a by-product of grouper which is underutilized so that it is of low value in the market and as a resource. The high protein content of fish offal can be used as a raw material in the manufacture of protein hydrolysates which of course require the role of proteolytic enzymes. Bromelain enzyme which is a proteolytic enzyme that is protease. This study aims to determine the effect of the bromelain enzyme concentration obtained from pineapple crude extract on the quality of the protein hydrolyzate of grouper offal. The experimental design used in this study was a Factorial complete randomized design with different enzyme concentrations (4, 6, 8, 10). and 12%) and the difference in water bath time (4, 6, 8, and 10 hours). The results showed the bromelain enzyme concentration had a very significant effect on the yield and degree of hydrolysis of snapper offal, and observations of the proximate results showed the potential utilization of hydrolyzed protein of fish offal as a food source.